PARTAI POLITIK, FENOMENA DINASTI POLITIK DALAM PEMILIHAN KEPALA DAERAH, DAN DESENTRALISASI - Budhy Prianto (Publisia: Jurnal Ilmu Administrasi Publik, 2016)
This study aims to describe the practice of political dynasties emerged along the carrying out of regional head election, describe the role of political parties in that process, and to explain the impacts on decentralization. The research used qualitative approach with primary data source documentation that purposively selected from Kompas newspaper. Data was collected, processed, and analyzed based on news or information related to political parties, direct regional head elections, and the phenomenon of the rise of political dynasties in some areas. The results shows that the practice of democracy in the local election has grown into a double-edged sword; on the on hand it gives the political rights to be elected to individual or group, and on the other hand depriving political rights to selected individuals or groups. This is a necessary condition for the growth and proliferation of the phenomenon of dynastic politics in Indonesia. Not surprisingly, the emergence of oligarchy both within political parties and local government without sufficient competence in governance at the local government. As a result, the practice of collusion, corruption and nepotism (KKN) spread in almost all regions in Indonesia.DOI: https://doi.org/10.26905/pjiap.v1i2.436